Inovasi Pembelajaran Bahasa Arab: Analisis Metode Tarkib Terjemah di Pondok Pesantren Tahfidz Al Habibi - Baeha, Ja’alna Salwinur; Rahmawati, Andini; Hidayat, Muhammad Yazim; Nasution, Sahkholid (Indo-MathEdu Intellectuals Journal, 2025)
Innovation in Arabic language learning is an urgent need to improve the linguistic competence of students in the era of globalization. The tarkib translation method applied at the Tahfidz Al Habibi Islamic Boarding School presents an analytical and systematic approach in learning Arabic grammar through a combination of understanding sentence structure (tarkib) and translation. The purpose of this study is to discuss the tarkib method at the Tahfidz Al Habibi Islamic Boarding School as an innovation in Arabic language learning. The research method used is library research as the main method to analyze the application and effectiveness of the tarkib translation method in Arabic language learning at the Tahfidz Al Habibi Islamic Boarding School. The results of the analysis show that the tarkib translation method is able to improve students' cognitive abilities and understanding of the cultural context of Arabic. The advantages of this method lie in the systematic preparation of materials and their application in various learning situations, both in class and in the daily activities of the Islamic boarding school. The support of a conducive learning environment and the integration of technology also strengthen the effectiveness of this method. It was found that the translation tarkib method not only strengthens the language skills of students but also helps them internalize Islamic values ​​through comprehensive understanding of the text.